GANGGUAN PERTUMBUHAN MANDIBULA PADA JUVENILE RHEUMATOID ARTHRITIS - Ria Puspitawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Juvenile Rheumatoid Arthritis (JRA) is a systemic disease on childhood, which has chronic arthritis as its most prominent manifestation. One very common complication of JRA is growth disturbance. JRA involving temporomandibular joint usually result in mandibular growth retardation which eventually can lead to micrognathia, retrognathia, malocclusion and other mandibulofacial developmental aberrations. Factors considered to be the cause of these growth and developmental disturbances are: congenital, the disease's direct effect on the condyle, functional deficiency of the temporomandibular joint, duration, age of disease onset and type of the JRA and corticosteroid therapy. However, the mechanism for the mandibulofacial growth and developmental aberrations due to JRA are not fully understood. This literature review will discuss the hypotheses concerning mechanisms of those growth and developmental disturbances, especially based on clinical and radiographic studies on JRA cases.